Foresight Scanning: Future Directions of Clinical and Pharmaceutical Research - Brian C. Foster (Frontiers Media S.A., 2009)
Foresight Scanning: Future Directions of Clinical and Pharmaceutical Research. Brian C. Foster, Therapeutic Products Directorate, Health Canada, Ottawa, Ontario, Canada ABSTRACT The Canadian Society for Pharmaceutical Sciences Satellite Symposium on Foresight Scanning, May 26 and 27, 2008, Nordegg, Alberta, Canada, focussed on the future directions of clinical and pharmaceutical research. The symposium brought together a group of clinicians, regulatory scientists, researchers and students to examine where clinical, pharmaceutical, and regulatory science might be in 10 to 15 years. Industry, regulatory, analytical, and clinical perspectives were presented and discussed, as well as the impact of exogenous (indirect) and endogenous (direct) change drivers. Unconditional funding was provided by Bayer HealthCare; they had no input on the direction of the meeting or selection of speakers. It was envisioned that the more important endogenous drivers may not be new information or changes in technology, policy, regulation, or health care delivery, but amplification of long-term underlying trends by emergence of new technologies, convergence of existing technologies or new communication and collaboration vehicles such as Web 2.0.